(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Life as a fundamental human right from a Christian perspective. The divine gift, life, according to the teaching of the Church, is the supreme value of man on earth, because it is the premise of all other values, which express it and impose it in front of all of them, because man was made according to the image and likeness of God. Christian teaching gives to man, both physical and spiritual life, a special value over the ethical conceptions of antiquity that disregarded human rights or limited them to a small group of individuals. By the commandment of love, Christian teaching abolishes all social barriers between people. According to the Christian faith, God is the absolute life and the source of life, He has revealed Himself to us in Jesus Christ absolutely and through divine providence, He watches over the course of the life of every man and every people, and calls us to work with Him in the fight against everything which wants to destroy life and even against those who prevent the appearance of life on earth, destroying it prematurely.